بنيــة المدة الزمنية في رواية ذاكرة الجسد لـ : أحلام مستغانمي - الأطـرش, رابح (Sciences humaines, 2014)
تتعرض هذه الدراسة ببعض التفصيل إلـى المدد الزمنية المتوفرة في نص روايـة " ذاكرة الجسد " و المتمثلة  في المجمل  " sommaire" ، و الحذف "   ellipse" و الوقفـة "  pause"     و المشهد "scene" ، وكيفية بنينتها جماليا استنادا إلى مرجعية تاريخية مشفوعة بتخيل جمالي ، و تشظي زمني،  أكسبها نسيجا بنائيا أفضى إلى إنتاج نص روائـي  زاوج بين الجمالي          و الإيديولوجي بامتياز    This study deals in some details with the duration found in « dakirat el djasat »represented in the summary ¸the ellipsis ¸the pause¸ and the scene¸  and how to structure it esthetic basing on some supported historical background with esthetic imagination ¸and broken time which gave it a structure tissue . This resulted in novelistic text that exellently linked bettween the esthetic and the ideological sides